O espaço da fruição literária na constituição do discurso pedagógico da leitura - Gonçalves , Sarah Suzane Amâncio Bertolli Venâncio (2017)
This work has as its object the literary enjoyment in the formation of the pedagogical discourse and the subject-reader in the initial years of Basic Education. Its main objective is to analyze what would be the space destined to enjoyment in the official documents that guide the curriculum and the teaching practice. To carry out this study, we consider reading in the discursive perspective (Orlandi, 2006; Bakhtin, 2011) and historical (Chartier, 2011; Manguel, 1997). The methodological strategy employed was the discourse analysis, expressed through the problematization of statements and the observation of the relations between documents and theoretical researches of reading. Our analysis questions whether the current reading practices in the school are contributing to the formation of the reader and, for that, we observe how reading comprehension skills, reading strategies and literary enjoyment are present in the MEC documents. We found that the formation of readers in Elementary School should include literacy literacy and reading-fruition, a potential agent for the constitution of readers, reaffirmed with more intensity in this phase, also because it acquires the habit of reading even in childhood. We conclude that in this age group it is possible for the subject to develop as an active reader (Bakhtin), critic (Orlandi), competent (PCN), model (Echo) and expert (Wolf and Barzillai) - and other nomenclatures used by theoreticians Scholars of this object, that is, the one capable of constructing the meanings of the text.